POLA KOMUNIKASI MENTOR BICARAPEDE ACADEMY DALAM PELATIHAN EXCLUSIVE OFFLINE CLASS PUBLIC SPEAKING - Ade Rina Farida (Yayasan Formadana Tabagsel Indonesia, 2025)
Public Speaking is needed in its application. The BicaraPede academy is a platform that focuses on self- development in the realm of public speaking, accompanied by certified professional mentors. The purpose of the research is to understand and know the communication patterns used by the mentors of BiacaraPede Academy and to know the dominant communication patterns in the application of exclusive offline class public speaking training. This research uses Joseph A. Devito's communication pattern theory, consisting of Y, wheel, circle, star and chain patterns. The method in the research is a case study while data collection includes observation, interviews, analysis and documentation. The results showed that the communication patterns used were star and circle communication patterns as well as linear, primary, and circular as supporting communication patterns. Meanwhile, the dominant patterns are circular and star patterns. Participants and mentors have the same rights or power to influence each other. The occurrence of a reciprocal process in the form of an active response that can lead to changes can be said that communication is effective.